The Compliance with Tarjih Fatwa on the -18° Dawn Criterion: A Study of Muhammadiyah Mosques in Gowa Regency - Fikri, Mursyid; Indriana; Syarif, Muh. Rasywan; Lubis, Arjuna Hiqma (MUI Sulawesi Selatan, 2025)
Differences of opinion regarding the determination of dawn time in Indonesia have become increasingly prominent, especially after Salafi groups claimed that the dawn time determined by the Ministry of Religious Affairs (KEMENAG RI) using the -20° criterion is 15–23 minutes too early. In response, Muhammadiyah conducted further research based on the recommendations of the 27th National Conference of Tarjih (Munas Tarjih) held on April 1–4, 2010. The research led to the Tanfidz Decision of the XXXI Tarjih National Conference, which concluded that the previously used dawn criterion was too early by about 8 minutes. As a result, Muhammadiyah adopted the -18° criterion as a more accurate standard and instructed all levels of its organization to follow this guideline in determining prayer times. This study aims to analyze the level of understanding and compliance among Muhammadiyah members regarding the Tanfidz Decision on the -18° dawn criterion. It also seeks to identify the obstacles faced in implementing the decision, particularly by mosque administrators in Muhammadiyah mosques in Gowa Regency. Using a qualitative approach and a case study method, data were collected through in-depth interviews and observation of dawn time practices. The findings show that most Muhammadiyah members in Gowa Regency understand and comply with the new guideline. However, several technical and social challenges remain, including limited access to precise observational tools and varying levels of understanding among mosque administrators. Nevertheless, the majority of Muhammadiyah mosques have made efforts to implement the -18° criterion in accordance with the directives of the Muhammadiyah Central Leadership.